Методичний підхід щодо розподілення витрат на утримання інфраструктури залізничнго транспорту (препринт) - Бараш, Юрій Савелійович; Савицька, Таїсія Миколаївна (Український державний університет залізничного транспорту, Харків, 2016)
UK: В статті запропонований підхід щодо удосконалення класифікації витрат на забезпечення функціонування інфраструктури залізничного транспорту, яка направлена на ефективне та науково-обґрунтоване ціноутворення. Дана класифікація враховує особливості технологічних процесів утримання та ремонту інфраструктури, характерних параметрів рухомого складу та об’єктів інфраструктури та дозволяє справедливо визначати собівартість послуг інфраструктури на основі конкретного впливу кожного поїзда на утримання та знос інфраструктури.

RU: В статье предложен подход по усовершенствованию классификации расходов на обеспечение функционирования железнодорожного транспорта, которая направлена на эффективное и научно-обоснованное ценообразование. Данная классификация учитывает особенности технологических процессов содержания и ремонта инфраструктуры, характерных параметров подвижного состава и объектов инфраструктуры и позволяет справедливо определять себестоимость услуг инфраструктуры на основе конкретного влияния каждого поезда на содержание и износ инфраструктуры.

EN: Classification of railway infrastructure costs has been improved in this article. It takes into account the characteristics of the infrastructure and rolling stock, features of technological processes to ensure the functioning of the railway infrastructure, the intensity of passenger and freight transport, the ratio of fixed and variable costs. This will determine the cost of infrastructure services, depending on the direct impact of each train for wear and tear of infrastructure. A new technique has been proposed in the work that has been developed on the basis of the separation fixed and variable costs of railways departments. It is based on the distribution of the current schedule of expenditure items, taking into account factors affecting their value. The introduction of this technique will allow to rightly determine the cost of infrastructure services based on the specific impact of each train on maintenance and wear and tear of infrastructure, to ensure the transparency of costs distribution and non-discriminatory access to rail infrastructure, will enable operators to choose tariff with regard to characteristics of infrastructure and rolling stock .
Методический подход к рапределению расходов на содержание инфраструктуры железнодорожного транспорта (препринт)
Methodic Approach to Railway Infrastructure Cost Allocation (preprint)
Ю. Бараш: ORCID 0000-0001-5911-9805,
Keywords: інфраструктура; витрати; собівартість; обсяг перевезень; швидкість; інтенсивність перевезень; инфраструктура; расходы; себестоимость; объем перевозок; скорость; интенсивность перевозок; infrastructure; cost; traffic volume; speed; traffic intensity; КОАІВ